PERHITUNGAN BIAYA PRODUKSI USAHATANI PADI PADA PETANI DI KABUPATEN BATUBARA - Yulifati Laoli; Diena Fadhilah; Supaino Supaino (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
In the agricultural sector, the cost production structure determines the income level of the farmers as well as the industry competitiveness in the world market. Considering the position of rice as the main food commodity for Indonesian people. This study aims to describe the paddy farming activities in Batubara Regency and to analyze the cost structure of paddy production in Batubara Regency. A survey was conducted in five production centre areas involving 100 farmers. The results showed that modern technology is used in rice farming. Land costs and labour costs dominate the cost structure of rice production. Meanwhile, the total production cost has reached 22.518.314,86 IDR per hectare with the cash cost percentage is 72,17 % and the non-cash cost percentage is 27,83 %.